Orofacial pain of cardiac origin: Review literature and clinical cases - López-López, José (Medicina Oral S.L., 2012)
The most common types of orofacial pain originate at the dental or periodontal level or in the musculoskeletal structures. However, the patient may present pain in this region even though the source is located elsewhere in the body. One possible source of heterotopic pain is of cardiac origin. Objectives: Report two cases of orofacial pain of cardiac origin and review the clinical cases described in the literature. Study Design: Description of clinical cases and review of clinical cases. Results and conclusions: Nine cases of atypical pain of cardiac origin are recorded, which include 5 females and 4 males. In craniofacial structures, pain of cardiac origin is usually bilateral. At the craniofacial level, the most frequent location described is in the throat and jaw. Pain of cardiac origin is considered atypical due to its location, although roughly 10% of the cases of cardiac ischemia manifest primarily in craniofacial structures. Finally, the differential diagnosis of pain of odontogenic origin must be taken into account with pain of non-odontogenic origin (muscle, psychogenic, neuronal, cardiac, sinus and neurovascular pain) in order to avoid diagnostic errors in the dental practice as well as unnecessary treatments. Key words:Orofacial pain, ischemic heart disease, heterotopic pain, odontalgia.